The illness as life. Ways of overcoming the irreversible on the example of maladic stories about children and for children of Katarzyna Ryrych - Chłosta-Zielonka, Joanna Maria (Porównania, 2023)
The article analyzes maladic stories about children and for children by Katarzyna Ryrych: Siedem sowich piór, Pepa w raju, Lato na Rodos and Wyspa mojej siostry. The aim of the analysis is to answer the question of how to tell the youngest audience about the liminal experience of a chronic, incurable and fatal disease. The child recipient treated subjectively and with respect for the right to know the truth about the world and its threats, should be prepared to talk about difficult topics. The possibility of overcoming the irreversible experience of a (fatal) disease will be discussed by talking about it directly, and sometimes by metaphorizing it. Children’s disease becomes a transformed form of life, enriched with important experiences.